HUBUNGAN SHIFT KERJA TERHADAP STRESS KERJA KARYAWAN PT ASTRA REKAYASA UNGGUL BALIKPAPAN - Saputera, Dharma; Siboro, Impol; Putra, Junaidi Ananda (Program Studi Kesehatan dan Keselamatan Kerja, 2022)
A sound psychological condition can indirectly impact how successfully and continuously the business's operations continue. System failures in a business can be caused by psychological issues, particularly stress, which lowers productivity. In order to better understand this relationship, a study was done on the employees of PT Astra Rekayasa Unggul Balikpapan. A sample is used as the research methodology in this case. This sampling approach uses total sampling to represent the 32 warehouse staff members at PT. Astra Rekyasa Unggul in this investigation. Between July and September 2020, morning and evening work shifts will be performed utilizing the DASS (Depression Anxiety Stress Scales) Measurement Tool Questionnaire. is divided into three categories: minor, medium, and major stress. According to the findings, out the 32 13 employees of PT. Astra Rekayasa Unggul who reported light stress fell into the moderate stress category, making up 81.25% of the total, with just 6 employees (37.5%) falling into the high stress category. The findings of the linear regression test showed that there is a significant correlation between work shifts and job stress on employees of PT Astra Rekayasa Unggul Balikpapan, with a probability lower than the significance level of 0.05. According to research's findings, efforts must be taken to lessen job stress caused by the effect of working shifts, specifically by tightening restrictions or dividing shifts.